Influence of N-type μc-SiOx:H intermediate reflector and top cell material properties on the electrical performance of “micromorph” tandem solar cells - P. Chatterjee; P. Roca i Cabarrocas (AIP Advances, 2018)
Amorphous silicon (a-Si:H) / micro-crystalline silicon (μc-Si:H), "micromorph" tandem solar cells have been investigated using a detailed electrical - optical model. Although such a tandem has good light absorption over the entire visible spectrum, the a-Si:H top cell suffers from strong light-induced degradation (LID). To improve matters, we have replaced a-Si:H by hydrogenated polymorphous silicon (pm-Si:H), a nano-structured silicon thin film with lower LID than a-Si:H. But the latter’s low current carrying capacity necessitates a thicker top cell for current-matching, again leading to LID problems. The solution is to introduce a suitable intermediate reflector (IR) at the junction between the sub-cells, to concentrate light of the shorter visible wavelengths into the top cell. Here we assess the suitability of N-type micro-crystalline silicon oxide (μc-SiOx:H) as an IR. The sensitivity of the solar cell performance to the complex refractive index, thickness and texture of such a reflector is studied. We conclude that N-μc-SiOx:H does concentrate light into the top sub-cell, thus reducing its required thickness for current-matching. However the IR also reflects light right out of the device; so that the initial efficiency suffers. The advantage of such an IR is ultimately seen in the stabilized state since the LID of a thin top cell is low. We also find that for high stabilized efficiencies, the IR should be flat (having no texture of its own). Our study indicates that we may expect to reach 15% stable tandem micromorph efficiency.